A132 ENDOSCOPIC ULTRASOUND-GUIDED GASTROENTEROSTOMY USING A NOVEL DOUBLE BALLOON DEVICE IN THE MANAGEMENT OF MALIGNANT GASTRIC OUTLET OBSTRUCTION. (4th March 2021) - Marino, A; Bessissow, A; Valenti, D; Boucher, L; Miller, C; Forbes, N; Chaudhury, P; Martel, M; Chen, Y
Abstract: Background: EUS-gastroenterostomy (EUS-GE) is a novel modality in the management of malignant gastric outlet obstruction (MGOO). It is, however, technically challenging limiting its widespread application. To facilitate EUS-GE, a double balloon catheter has been developed in Japan. While this tool is not available outside of Asia, we have conceived a similar device using a widely available vascular balloon catheter. We aim to determine the clinical efficacy and safety of EUS-GE using this double balloon device (DBD). Aims: We aim to determine the clinical efficacy and safety of EUS-GE using this double balloon device (DBD). Methods: This is a single-centre, retrospective study of consecutive patients who underwent DBD assisted EUS-GE for MGOO from January 2019-June 2020 (IRB approved). The DBD consists of two 60 mm vascular balloons (Coda, Cook Medical, USA) fashioned together with the balloons 10 cm apart (Figure 1). It is inserted across the obstruction over a wire to the ligaments of Treitz. Both balloons are then inflated followed by saline and contrast infusion into the occluded small bowel segment to facilitate EUS-guided insertion of a 15 mm cautery assisted lumen apposing metal stent (Axios TM, Boston Scientific Inc, USA). The primary endpoint is the rate of technical success defined as adequate deployment of the stent. Secondary endpoints include rate of clinical success and adverse events. Results: A total of 11 patients were included in this study. 45% were female with a mean age of 64.9 ± 8.6 years old. The etiology of MGOO was 73% pancreatic cancer, 9% gastric cancer, 9% duodenal cancer, and 9% metastatic cervical cancer. Procedures were performed under general anesthesia and conscious sedation in 82% and 18%, of patients respectively. The mean procedure time was 64.8 ± 25.8 minutes. Technical and clinical success (intention to treat) was 91%. The only technical failure was due to poor patient tolerance of the procedure under conscious sedation. There was one adverse event (9%) due to stent migration rated as severe. Two patients (18%) required re-intervention for stent obstruction secondary to food impaction associated with non-compliance to a low-residue diet. Following re-enforced instructions, no further obstruction occurred. All patients started a clear liquid diet within 1 day of the procedure with a mean time to a low residue diet of 3.25 days ± 2.5. The median length of hospital stay following the procedure was 5 days ± 13. The median follow-up time was 84 days (IQR 152). Conclusions: DBD assisted EUS-GE is clinically effective and safe. This balloon device may greatly facilitate the technical aspect of EUS-GE while potential enhancing its safety and clinical use. Larger studies are needed to validate this approach to EUS-GE. Funding Agencies: None